The Evaluation of Supporting Capability and Development Strategy of Selili Fish Landing Base, Samarinda City - Wahab, Hadi Syaukani; Gunawan, Bambang Indratno; Almadi, Ismail Fahmy; Fitriyana, Fitriyana; Purnamasari, Elly; Juliani, Juliani (Agrikan Jurnal Agribisnis Perikanan, 2023)
This study aims to assess the Supporting Capability of the Selili Fishing port in basic, functional and supporting facilities so as to provide useful information to all stakeholders who are doing business at the Selili fish landing base and develop a development strategy for the Selili Fishing port. The method used in this research is descriptive method. Sampling using purposive sampling method by collecting primary data and secondary data. The analysis method used is SWOT analysis to evaluate internal and external factors in developing development strategies. The results of this study indicate that the facilities at PPI Selili can support fisheries activities in Samarinda city. Based on the analysis of internal and external factors, known that Selili Fishing port infrastructure has not been optimally managed. Based on SWOT analysis, the position of PPI Selili is in quadrant I, where in this quadrant is used as a priority strategy, namely improving PPI facilities and optimizing their use by utilizing community & government support. Increase the volume of fish production and optimize its use by utilizing community & government support. Increase the volume of fish production and its quality by strengthening cooperation with fish-producing areas in order to meet the ever-increasing needs of the community. Maximize fish marketing at fish landing sites by expanding the fish marketing and distribution network in the Samarinda City area and other district. Improve and strengthen the quality of human resources of PPI managers and all people who are active in PPI through targeted guidance and training.